Identification Of Potentialantibiotics – Drugs interaction On Pneumonia Prescription - Yeni Farida; Anisa Dewi Soleqah (JPSCR: Journal of Pharmaceutical Science and Clinical Research, 2016)
Pneumonia is lower respiratory tract infections, which is the leading cause of death in developing countries. Antibiotics are the primary therapy in cases of pneumonia due to bacteria. The use of antibiotics with other drugs allowing harmful effect. This study aimed to determine the significancy of antibiotics interaction and determine the phase of potential drug interaction could be happened.Data were collected retrospectively by taking data on the patient's medical record. Samples were obtained by purposive sampling. Inclusion criteria were patients diagnosed  pneumonia with comorbid and got antibiotic therapy.The results showed that there were 12 types of drugs combinationthat could potentially cause drug interactions .Potential interactions with other drugs antibiotics based on the literature occurred in the absorption phase (12.82%), metabolism (35.9%), and excretion (51.28%).